Investigating an alternative sustainable low-enriched uranium target for the manufacture of 99Mo using MCNP6.2 modelling with CINDER90 - Raposio, Robert; Braoudakis, George; Rosenfeld, Anatoly; Thorogood, Gordon; Bedwell-Wilson, Juniper (Frontiers in Nuclear Engineering, 2023)
Current fission-based methods of 99Mo production use targets that are based on high output without taking into consideration the amount of radioactive waste produced. We examine the idea of using a low enriched target (<20%) in an attempt to reduce the amount of nuclear and chemical wastes produced by the manufacture of 99Mo via fission of uranium-based targets. MCNP6.2 was used to model targets of 20%, 10%, 7%, 3% and 1% enrichment for 99Mo output and sustainability. The 1% enriched target at the lowest density of 0.2 g/cm3 of UO2 was found to have the highest sustainability score at 6 days irradiation but it had a low 99Mo output. On the other hand, the highest output target was found to be 20% enriched with a density of 8.0 g UO2/cm3 with an irradiation time of 20 days. Target security and safeguards concerns were modelled and found to be of minimal concern.